Effects of irrigation, plantation density and clonal composition on woody biomass quality for bioenergy in a short rotation culture system with willows (Salix spp.) - Achinelli, Fabio Germán (2018)
A short rotation intensive system with willows was analyzed with the following aims: a - to determine the effects of irrigation, genotype and plantation density on wood anatomy, wood density, moisture content, lower heating value, total ash content and energy accumulated in the woody biomass; b – to explore the relationships between anatomical and physical wood properties and the parameters determining their quality as a biofuel. A complete factorial experiment was set up, with three factors and two levels for each factor. The factors were: irrigation, plantation density and clone (genotype). The clones were Salix matsudana Koidz. x Salix alba L. ‘Barrett 13-44 INTA´ (B) and Salix alba L. ‘Yaguareté INTA - CIEF´ (Y). 46 stools of 1 m long were sampled, on which the following determinations were carried out: vessel diameter and frequency, fiber wall thickness and area, wood density, moisture content, ash content and heating values. Clone B had higher wood density than clone Y (0.406 vs. 0.395 g/cm3) and lower moisture content (47.11 vs. 50.53 %). The plantation density did not affect any of the variables analyzed. Irrigation increased the energy yield to 393.2 Gj/ha, compared to 309.15 Gj/ha without irrigation. A system with clone B planted at a lower density (13,000 plants/ha) and under irrigation has the best advantage as an energetic crop over the other alternatives evaluated in this work.